Mullerian Duct Cyst in Vagina Mimicking as Rectocele - Bhatara, U; Padmasri, R; Begum, R (Nepal Journal of Obstetrics and Gynaecology, 2016)
Mullerian duct cysts of vagina are rare. Precise diagnosis of Mullerian cyst of vagina requires clinical, radiological and histopathological examination. Here case of Mullerian cyst is presented which was mimicking rectocele and main complaint during presentation was difficulty in intercourse.